Farmer participatory evaluation of four hybrid water yam clones in the yam belt of Nigeria - Ikeorgu, J.G.; Oselebe, H.; Oluwatayo, J.; Ugwuoke, K.; Ukpabi, U.J.; Asiedu, Robert (2009)
Four hybrid water yam (Dioscorea alata) genotypes (TDa 00/00194, TDa 00/00103, TDa 00/00104, TDa 00/00363) with two superior landraces (TDa 92-2 and UM 680) were evaluated for high and stable yields, pest and disease resistance, and acceptable food and market qualities in 2006 using the farmer participatory (FP) approach. This researcher managed trial was carried out in Umudike (humid forest), Abakaliki and Nsukka (derived savanna), and Makurdi (southern Guinea savanna). Farmers participated in evaluating the genotypes for physiological attributes, yield, and eating qualities during mid-season (August/September) and at harvest. The hybrid yams gave almost twice the tuber yield of the landraces. Also the landraces were scored higher than the landraces in terms of pest and disease resistance, plant canopy, leaf litter, etc. In terms of food quality, TDa 00/00194 (4.0) was rated a little higher than the local best UM 680 (3.9) though this did not differ from TDa 00/00104 (3.5). Results from sensory evaluation and palatability tests showed that TDa 00/00194 and TDa 00/00364 had the highest rating in food quality for amala preparation. In selecting water yams therefore, consideration should be based on sensory acceptance, high dry matter, and low peel loss.